Performance test differences and paralympic team selection: Pilot study of the United States national wheelchair rugby team - Barfield, J. P.; Malone, L. A. (International Journal of Sports Science and Coaching, 2012)
The purpose of this study was to determine if differences existed on performance tests between wheelchair rugby players who were and were not selected for a national team. The sample was selected from prospective national wheelchair rugby team members (n = 27) and delimited to match selected and non-selected team members on functional rugby classification. Performance tests consisted of mile-pushes, endurance sprints, slaloms with and without a ball, full-court sprints, up & backs, and short and long passing for accuracy. Selected team members had significantly better mean scores on several performance tests (p < 0.05) with the greatest effect sizes realized on physical fitness components. Distinctions between athletes selected for a national wheelchair rugby team and those not selected were nited fpr performance tests with physical fitness components. Coaches are encouraged to include fitnessrelated tests as a part of their regular training strategies.